Community Health Outreach Camps' Influence on Medical Education (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Camps for community health outreach have become an important and game-changing part ofmedical education. The transitory nature of these camps, which provide healthcare to impoverishedpopulations, is a major factor in helping to close the gap between classroom instruction and actual patientcare. The incorporation of community health outreach camps into medical school is a proactive reaction tothe ever-changing issues and possibilities presented by the next generation of healthcare professionals. InThis research explores the effects of community medical camp volunteering on the clinical and soft skills,understanding of community health, and career aspirations of medical students and recent graduates.The Aldar Hospital in Saudi Arabia was the site of the pilot cross-sectional research. Participants'answers were gathered using a self-reported online survey. SPSS 25 was used to analyse the data.